2017
DOI: 10.1007/s12154-017-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of a new steroid-macrocyclic derivative with biological activity

Abstract: The aims of this study were to evaluate the positive inotropic effect of a new macrocyclic derivative (compound 11) and characterize the molecular mechanism involved in its biological activity. The first step was achieved by synthesis of a macrocyclic derivative involving a series of reactions for the preparation of several steroid derivatives such as (a) steroidpyrimidinone (3 and 4), (b) steroid-amino (5), (c) steroidimino (6), (d) ester-steroid (7 and 8), and (e) amido-steroid (9 and 10). Finally, 11 was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The results showed that only compound 4 (Dibenzo[b,e]thiophene-11(6H)-one) significantly increases perfusion pressure in a time-dependent manner compared to compounds 1-3, 5-10 and the control conditions. These data suggest that Dibenzo[b,e]thiophene-11(6H)-one could produce changes in the coronary resistance such happening with other type of compounds [32,33]. Based on these data, in this study the biological activity produced by Dibenzo[b,e]thiophene-11(6H)-one on coronary resistance was evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that only compound 4 (Dibenzo[b,e]thiophene-11(6H)-one) significantly increases perfusion pressure in a time-dependent manner compared to compounds 1-3, 5-10 and the control conditions. These data suggest that Dibenzo[b,e]thiophene-11(6H)-one could produce changes in the coronary resistance such happening with other type of compounds [32,33]. Based on these data, in this study the biological activity produced by Dibenzo[b,e]thiophene-11(6H)-one on coronary resistance was evaluated.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, experimental protocols were reviewed and approved by the Animal care and use committee of University Autonomous of Campeche (UAC) and were in accordance with the guide for the care and use of laboratory animals [15].…”
Section: Animalsmentioning
confidence: 99%
“…The second stage was achieved by the synthesis of an ether-steroid derivative (3); it is important to mention that some reports have been reported for the preparation of ether derivatives via displacement of nitro group using methoxide as dipolar aprotic solvent [21,22]. In this study, 3 was prepared using a previously method reported [23]; the reaction was carried out through intramolecular displacement from nitro group by the hydroxyl group of the compound 2 in presence of DMSO/K 2 CO 3 (Figure 1). The 1 HNMR showed several signals for 3 at 0.90 ppm for methyl group bound to steroid nucleus; at 1.18 ppm for methyl bound to oxazole ring; at 1.22-3.10 and 6.43-6.54 ppm for steroid moiety; at 6.24 ppm for oxazole ring; at 7.72 for both hydroxyl and amine groups.…”
Section: Physicochemical Parameters Evaluationmentioning
confidence: 99%